Analisis Tantangan Keamanan Data dan Privasi dalam Adopsi Aplikasi Kesehatan Digital di Indonesia - Abim Sastrawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2025)
Digital health applications offer significant potential for improving healthcare access and efficiency, but their widespread adoption raises major concerns regarding data security and privacy, especially with the utilization of health big data. These applications collect and process highly sensitive information, such as health history and biometrics, making them attractive targets for cyber threats like identity theft and fraud. This study aims to analyze the key data security and privacy challenges in digital health adoption with a focus on big data utilization. Employing a descriptive qualitative method, secondary data from academic literature and regulations were analyzed through thematic content analysis. Findings reveal major vulnerabilities, including weak technical protection, low regulatory compliance, and minimal user awareness of digital risks. Big data is identified as both a risk and a mitigation tool, depending on its ethical management. The conclusion emphasizes that strengthening digital literacy and regulatory enforcement (e.g., UU PDP No. 27/2022) are crucial for building public trust in digital health technology adoption. Further research using mixed-method approaches is recommended for deeper empirical insights.